Surface deformation and its implications for land degradation after the 2021 Flores earthquake (M7.4) using differential interferometry synthetic aperture radar - Purba, Joshua; Harisma, Harisma; Priadi, Ramadhan; Amelia, Rosa; Dwilyantari, Anak Agung Istri; Jaya, Laode Muhammad Golok; Restele, La Ode; Putra, I Made Wahyu Gana (Brawijaya University, 2024)
On December 14, 2021, an earthquake with a magnitude of 7.4 originated from the Flores Sea, impacting Kalaotoa Island in Indonesia, resulting in significant structural damage. Macroseismic observations at the site classified that there were 120 buildings slightly damaged, 108 buildings moderately damaged, and 201 buildings heavily damaged. The shakemap shows that Kalaotoa Island experienced VI-VII MMI shaking. The results of the field survey showed many indications of subsidence as many fractures were found in Kalaotoa Island. This study employed Differential Interferometry Synthetic Aperture Radar (DInSAR) to quantify land subsidence and uplift in Kalaotoa Island before and after the earthquake. Sentinel-1A satellite radar data from December 2 and December 14, 2021, were analyzed. The results revealed subsidence of up to 12 cm in Garaupa Raya Village and uplift of up to ±10 cm in Lembang Mate’ne Village. Approximately 50.50% of Kalaotoa Island experienced subsidence (39.4 km²), primarily in Garaupa Village (18.85 km²), while 49.02% of the island experienced uplift (38.2 km²), mostly in Lembang Mate’ne Village (19.03 km²). This spatial analysis underscores the efficacy of DInSAR in detecting and mapping surface deformation, offering critical insights for earthquake preparedness, mitigation efforts for impacted landscape topography, stability soils, structure of ecosystems, and infrastructure resilience.